Excess respiratory viral infections and low antibody responses among HIV-exposed, uninfected infants. (13th March 2017) - Weinberg, Adriana; Mussi-Pinhata, Marisa M.; Yu, Qilu; Cohen, Rachel A.; Almeida, Volia C.; Amaral, Fabiana; Pinto, Jorge; Teixeira, Maria L.B.; Succi, Regina C.M.; Freimanis, Laura; Read, Jennifer S.; Siberry, George
Abstract : Objective: HIV-exposed uninfected (HEUs) infants have frequent severe infection, hospitalization, and death. We performed a serologic investigation to determine the role of common childhood respiratory pathogens in the excess incidence of infections in HEUs. Design: Prospective cohort study of mother–infant pairs. Methods: Among 247 HEUs and 88 HIV-unexposed uninfected (HUU) infant–mother pairs, we measured maternal antibodies to respiratory syncytial virus (RSV) and pneumococcus (PNC 1, 5, 6B, 14); infant antibodies to RSV, influenza A (flu), parainfluenza viruses (1, 2, 3), and PNC 1, 5, 6B, and 14 were measured at 0 and 6 months, and antitetanus antibodies at 6 months. Results: HIV-infected mothers had higher RSV and lower PNC antibody concentrations at delivery than uninfected mothers. Transplacental transfer of maternal antibodies, particularly for RSV, was lower in HEUs compared with HUUs. At birth, HEUs had higher concentrations of anti-RSV antibodies than HUUs, but lower antibodies to the other respiratory agents. At 6 months, HEUs had significantly higher proportions of seroconversions and higher antibody concentrations against parainfluenza viruses 1, 2, and 3. There were no significant differences in seroconversions to flu and RSV, but antibody concentrations to RSV were six-fold lower in HEUs versus HUUs at 6 months. Antibody responses to at least two doses of tetanus vaccine were also six-fold lower in HEUs compared with HUUs. Conclusion: Six-month-old HEUs had a higher incidence of respiratory viral infections than HUUs. In addition to the low passive protection from maternal antibodies, low antibody responses of HEUs may contribute to increased morbidity and mortality. Abstract : Supplemental Digital Content is available in the text